Harnessing defects in Ag/CeO2 for enhanced photocatalytic degradation of antibiotic in water: Structural characteristics, in-depth insights on mechanism, degradation pathway - Ajit Kumar Dhanka; Emerson C. Kohlrausch; Raghabendra Samantray; Vinod Kumar; Balaram Pani; Nityananda Agasti (Chemical Engineering Journal Advances)
A highly efficient and stable CeO2-based material has been developed for photocatalytic degradation of antibiotics in water. In this study, we investigated the defects due to metal-support interaction between Ag and CeO2 in the Ag/CeO2 nanocomposites. Here we introduced oxygen vacancies in CeO2 by incorporating Ag on the surface of CeO2. Notably, the addition of Ag to CeO2 reduces the band gap energy to 2.90 eV, accompanied by an increase in Ce3+ content which is correlated with an increase in oxygen vacancies. X-ray photoelectron spectroscopy (XPS), Raman and EPR studies substantiated the increase in surface oxygen vacancies in CeO2 induced by the interaction between Ag and CeO2. Oxygen vacancies in Ag/CeO2 act as trapping sites for photogenerated electrons and successfully restrain the recombination of photogenerated electron and hole pairs, thereby exhibiting improved catalytic activity of Ag/CeO2 nanocomposites. Ag/CeO2 nanocomposites exhibited better catalytic performance than pristine CeO2, which is attributed to the enhanced oxygen vacancies in the nanocomposites. We investigated the effect of silver (Ag) on increasing oxygen vacancies in Ag/CeO2.Trapping experiments were conducted to identify the reactive species participating in the photocatalytic degradation process. A plausible mechanism is proposed based on critical analysis of the results from the characterization techniques of the nanocomposites and photocatalytic experiments. The possible degradation pathways for Ciprofloxacin along with the degradation intermediates have been proposed based on High resolution mass spectroscopy (HRMS) analysis. This study provides insights on structural characteristics of defective CeO2, in-depth photocatalytic mechanism and degradation pathway of ciprofloxacin, that could facilitate the exploration of other ceria-based nanocomposites for catalytic applications.